A TRPM4 Inhibitor 9-Phenanthrol Inhibits Glucose- and Glucagon-Like Peptide 1-Induced Insulin Secretion from Rat Islets of Langerhans - Zuheng Ma; Anneli Björklund; Md. Shahidul Islam (Journal of Diabetes Research)
Pancreatic β-cells express several ion channels of the transient receptor potential family, which play important roles in mediating the stimulus-secretion coupling. One of these channels, the TRPM4 is a Ca2+-activated monovalent cation channel. This channel is inhibited by 9-phenanthrol, which also inhibits the TMEM16a Cl− channel, and activates the Ca2+-activated K+ channel, Kca3.1. The net effects of ion-channel modulation by 9-phenantherol on the insulin secretion remain unclear. We tested the effects of 9-phenanthrol on glucose- and GLP-1-induced insulin secretion from isolated rat islets in static incubations. When applied to the islets in the presence of 3.3 mM glucose, 9-phenanthrol caused a small increase in insulin secretion (~7% of the insulin secretion stimulated by 10 mM glucose). 10 μM 9-phenanthrol did not inhibit glucose- or GLP-1-induced insulin secretion. 20 μM and 30 μM 9-phenanthrol inhibited glucose-induced insulin secretion by ~80% and ~85%, respectively. Inhibition of the GLP-1-induced insulin secretion by 20 μM and 30 μM 9-phenanthrol was 65% and 94%, respectively. Our study shows that the major effect of 9-phenanthrol on the islets is a strong inhibition of insulin secretion, and we speculate that compounds related to 9-phenanthrol may be potentially useful in treating the pancreatogenous hyperinsulinemic hypoglycemia syndromes.